Ascent : designing characters in an action horror game about Chinese LGBTQ+ survival and power : an exegesis presented in partial fulfilment of the requirements for the degree of Masters in Design at Massey University, College of Creative Arts, Wellington, New Zealand - Liu, Tianzi (Massey University, 2024)
In mainland China, activism and globalised discourse for LGBTQ+ rights have resulted in a growing backlash of tightened censorship and state-sponsored queerphobia. Discussions are muddled by nationalist rhetoric that villainises queerness as a fully “Western” idea, and effectively dismisses any diasporic Chinese queer perspectives - even China’s own queer history - justifying a push towards blanket heteronormativity. To be Chinese, queer and third culture means to exist uncomfortably in the gap between this East/West ideological war, while being seen as a threat to political stability by your home country and facing an increasingly hostile future environment. It is crucial to create queer Chinese media that acknowledges this complex third space, especially given the suppression of queer visibility in mainland China and a Western-dominated international LGBTQ+ media landscape. The reinterpretation of folktales can help reflect transforming culture in globalisation and with communicating transnationality, connecting present realities to traditional cultural identity through storytelling. There is a real ‘horror’ in being queer in an unaccepting, conservative Chinese society, but the queer spirit has always been to prevail against its oppressors – “fighting” against the horror. This project confronts the divide between queer and cultural identities and anxiety for the future, by imagining an action horror game set in a speculative dystopia and visualising this narrative through concept design. I will create a modern queer interpretation of the characters from the famous Chinese classic 西游记 /Journey to the West, as young prisoners trapped in a futuristic conversion facility. The game levels are based on the Buddhist 十八层地狱/”18 Levels of Hell” and are filled with machine beasts that are the distorted spirits of Chinese mythological creatures. The intention is to bridge queerness with Chineseness by combining modern queer imagery with elements of Chinese traditional culture, especially historically queer aspects such as Chinese Opera aesthetics – one of the oldest visual forms of storytelling for Chinese mythology. This research project involves examining queer discrimination in China, issues of queer representation, the legacy of folklore and narrative trends of popular media such as video games, to inform the design of characters and plotline in creating cathartic media for a diasporic Chinese LGBTQ+ audience that aims to be empowering.
Copyright holders of copyrighted images are invited to use the "Takedown Request Button" below to request their removal.
Keywords: 360502 Computer gaming and animation